2020
DOI: 10.1007/s00520-020-05579-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mucositis risk secondary to cancer therapy: a systematic review of current evidence and call to action

Abstract: peer review but prior to copyediting and typesetting that can be made available under the following conditions:(i) Author(s) retain the right to make an AAM of their Article available on their own personal, selfmaintained website immediately on acceptance, (ii) Author(s) retain the right to make an AAM of their Article available for public release on any of the following 12 months after first publication ("Embargo Period"): their employer's internal website; their institutional and/or funder repositories. AAMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 120 publications
0
35
1
2
Order By: Relevance
“…Sex has been reported to have an influence on mucositis risk because, in most studies, female sex is linked to increased risk 24 . However, this may be driven by dosimetric parameters (ie, calculating the risk per kilogram of body weight or per square meters of body surface area) 24,25 . An individual's low baseline performance status may be related to increased mucositis risk 25 .…”
Section: Oral Mucositis Associated With Cytotoxic Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex has been reported to have an influence on mucositis risk because, in most studies, female sex is linked to increased risk 24 . However, this may be driven by dosimetric parameters (ie, calculating the risk per kilogram of body weight or per square meters of body surface area) 24,25 . An individual's low baseline performance status may be related to increased mucositis risk 25 .…”
Section: Oral Mucositis Associated With Cytotoxic Regimensmentioning
confidence: 99%
“…An individual's low baseline performance status may be related to increased mucositis risk 25 . There is inconsistent evidence regarding the influence of age, smoking, oral hygiene, and body mass index on mucositis risk 24,26 . The risk of mucositis may be influenced by genetic variants in drug‐metabolizing pathways, immune signaling, and cell injury‐repair mechanisms, although the evidence is limited or conflicting (see Supporting Table ).…”
Section: Oral Mucositis Associated With Cytotoxic Regimensmentioning
confidence: 99%
“…This has been most elegantly demonstrated in the case of immunotherapy-induced colitis [32e34]; however, a growing body of evidence anecdotally suggests that similar mechanisms may dictate an individual's risk of mucosal injury caused by chemotherapy [30]. In a recent systemic review of predictors of mucosal injury coordinated by the Multinational Association for Supportive Care in Cancer [11], antibiotic use in the month leading up to cancer therapy was identified as a modulator of mucosal injury [35,36]. Consistent with these findings, antibiotic administration before MTX treatment caused a profound increase in treatment-related mortality and diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, a growing body of evidence suggests that microbial disruption (i.e. caused by antibiotic use) at the time of chemotherapy increases the risk of adverse events linked to MBI, suggesting a causal role for the host microbiome [11].…”
Section: Introductionmentioning
confidence: 99%
“…The OMDQ is a self-reported instrument that can be an alternative clinical assessment if the patient refuses to do an oral examination by health practitioners [34]. A research conducted by Wardill et al reported that the NCI-CTC is an instrument that is more widely used in assessing oral mucositis in cancer patients, followed by the Radiation Oncology Research Group, the WHO mucositis scale, OMAS, Oral Mucositis Index, and OAG [35]. This research does not specify which one is the most effective instrument and more emphasize the importance of using a validated instrument in assessing mucositis.…”
Section: Discussionmentioning
confidence: 99%